LOW-COST METHODOLOGY FOR MONITORING MUNICIPAL LAND FILLS, BASED ON THE USE OF SATELLITE IMAGES - Fernando SERNAQUE , Wilver AUCCAHUASI (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Caring for the environment is one of the main criteria in the administration of cities, therefore it is necessary to have places where waste generated in cities is managed, between the optimal and the real there is a lot of difference This is why in many countries and with emphasis on large cities, there are unofficial places where they are used as municipal dumps, where large tons of solid waste are disposed of daily without going through a selection and recycling mechanism. These dumps are growing out of control and are almost becoming able to live with people. In the present work it is proposed to present a methodology to be able to monitor these dumps and be evaluated from space through the eyes of the observation satellites, which generate satellite images, the methodology proposes a temporary review of the area where the dumps are located In order to monitor its growth and analyze when it puts the urban population at risk, the results are evaluated in the municipal dump called "El Milagro" located in the vicinity of the city of Trujillo located north of Lima, Peru , the City of Trujillo is one of the main cities of Lima, located to the north, it is in the vicinity of this city where one of the largest dumps in Peru is developed. The results show that with the use of satellite images, the growth of these dumps and their impact on the community can be verified